Africa Media Review, Volume 17, no 1 & 2, 2009: Special Issue on Peace and Communication in Post-conflict Africa - journal system, (Africa Media Review, 2009)
Contents Introduction: Peace and Communication in Post-conflict Africa Eddah Mutua-Kombo ....................................... 1 Introduction : Paix et communication dans les zones post-conflit en Afrique Eddah Mutua-Kombo .................................. 5 Theorizing Post-conflict Peace Communication: Can Rwandan Women’s Narratives of Sexual Violence become the Point of Departure for Research? Eddah Mutua-Kombo .................................................... 9 The Semantics of Peace and the Role of the Print Media in the 2007-2008 Post-election Violence in Kenya Benson Oduor Ojwang ...................................... 23 Media Image and Social Integration of Liberian and Togolese Refugees in Ghana Heidi G. Frontani, Kristine Silvestri & Amanda Brown ........................... 51 The Politicization of the Education System: Implications for Peace in Sudan Hala Asmina Guta..................................... 77 Silent Religiosity in a Sniveling Nation: The Role of Religious Institutions in Promoting Post-conflict Reconciliation in Kenya Susan M. Kilonzo ......................................... 95 Somali Language and Oral Tradition in Post-conflict Life in the U.S: What Does the Future Hold? Sarah Drake & Eddah Mutua-Kombo ....................................... 109 Book Review Confronting Ethnic Conflict: The Role of Third Parties in Managing Africa’s Civil Wars by Jennifer L. De Maio, Lexington Books, 2009 Sakile K. Camara & Darlene Drummond ................................. 123